A socio-constructivist framework for tactical development in team sports: fostering critical thinking through collaborative learning - Gaviria Alzate, Samuel Jose Octavio; Valencia Sánchez, Wilder; Arias, Elkin Arias (Frontiers in Psychology, 2025)
In team sports, tactical success depends not only on players' individual skills but fundamentally on their ability to engage in meaningful social interactions and shared understanding. This study introduces the Tactical Program based on Critical Thinking (TPCT), a pedagogical framework grounded in socio-constructivist theory, aiming to foster the development of higher-order thinking skills essential for tactical decision-making. TPCT emphasizes processes such as interpretation, analysis, inference, evaluation, explanation, and self-regulation through guided reflection and collective dialogue. Rather than imposing predefined tactical solutions, the program promotes collaborative construction of strategic responses based on reflective discussion and mutual support among teammates. Coaches using the TPCT are provided with structured guidelines to design training sessions that prioritize communication, reasoning, and joint problem-solving. By fostering an environment where knowledge is co-constructed, the TPCT contributes to more autonomous, context-sensitive, and socially informed tactical behavior. This approach offers promising applications across various team sports, reinforcing the role of critical thinking in enhancing team coordination and intelligent gameplay.